Comparison of different doses of magnesium sulphate and fentanyl as adjuvants to bupivacaine for infraumbilical surgeries under subarachnoid block - Sarika Katiyar (Indian Journal of Anaesthesia, 2015)
Background and Aims: Spinal anaesthesia is used for many years for surgeries below the level of umbilicus. It has certain disadvantages such as limited duration of blockade and post-operative analgesia. This study was undertaken to evaluate the effects of additives fentanyl and magnesium sulphate along with bupivacaine during spinal anaesthesia for prolongation of analgesia and motor blockade. Methods: This randomised study was conducted in 120 patients of either sex of American Society of Anesthesiologists physical status I and II, posted for infraumbilical surgeries. Patients were randomly allocated to four groups and were given the following drugs intrathecally as per group distribution; group A - bupivacaine 15 mg (0.5% heavy) with fentanyl 25 μg, group B - bupivacaine 15 mg (0.5% heavy) with magnesium 100 mg, group C - bupivacaine 15 mg (0.5% heavy) with magnesium 50 mg and group D - bupivacaine 15 mg (0.5% heavy) with 0.5 ml normal saline. Parameters monitored were duration of analgesia along with haemodynamic parameters and side effects. Data were analysed using the Student′s t-test for the continuous variables and two-tailed Fisher exact test or Chi-square test for categorical variables. Results: There was significant increase in duration of analgesia in group A (374.37 min) and B (328.13 min) as compared to group C (274.87 min) and D (246.03 min). In group A, all haemodynamic parameters decreased by more than 20%, compared to baseline parameters, which was clinically and statistically significant as compared to other groups. There was also increase in duration of motor blockade in groups A and B. Conclusion: Addition of magnesium sulphate at 100 mg dose or fentanyl 25 μg as adjuvants to intrathecal bupivacaine significantly prolongs the duration of analgesia, though in the given doses, magnesium provides better haemodynamic stability than fentanyl, with fewer side effects.